Quality of honey from argentina: study of chemical composition and trace elements - Cantarelli, Miguel Angel (2008)
Content of P, Fe, Al, Mn, Zn, Cu, Ca. Mg, Na and K trace elements, as well as moisture, pH, free acidity, lactone, reducing sugar, sucrose, diastase activity, ashes and hidroximethylfurfural, were analyzed in 38 samples of natural honey from different places of the centre of Argentina. The mean values for element content were (in µg g-1): P: 28.80; Fe: 3.91; Al: 2.57; Mn: 0.33; Zn: 1.08; Cu: 0.19; Ca: 56.35; Mg: 23.38; Na: 25.56; K: 482.75. Pr was used as an internal standard in order to evaluate the recovery percentage of the trace elements. Chemical content shows the following media results: moisture 16.24 %; pH 3.85; free acidity 30.15 mg g-1; total acidity 31.65 mg g-1; reducing sugar 68.08 %; sucrose 4.05 %; diastase number 19.73, ashes 0.11 % and hidroximethylfurfural: 8.98 mg kg-1.